Global impact of urbanization on ecosystems: A comprehensive bibliometric analysis - Himadri Soni; Rajiv Kant Yadav; Suresh Kumar Patra (Natural Hazards Research)
This paper demonstrates a comprehensive assessment of bibliometric analysis of published research on the global impact of urbanization on environmental consequences. Scopus database was used to collect data on the global impact of urbanization on ecosystem research from 2000 to 2023 and scrutinizes the progression of publications, keyword analysis, co-citation of authors, citation of documents, co-authorship of authors, and most efficient and influential authors, countries, and institutions. A total of 4322 research papers (journals) were published during the period (2000–2023). This bibliometric study was carried out with the Vos Viewer software. The study's findings demonstrate that the number of publications has continuously increased between 2000 and 2023. In 2020 and 2022, there were 396 and 635 publications, respectively. The top three influential journals in terms of citations are Remote Sensing of Environment (2415 citations), Ecological Economics (1456 citations), and PLoS (1410). From 2000 to 2023, the most often appearing terms were urbanization (3028), urban area (1111), people (853), land use (769), environmental monitoring (594), environmental effect (570), sustainable development (567), and climate change (534). We created a time series with four periods (2000–2005, 2006–2011, 2012–2017, and 2018–2023) based on the periodic changes, which also shows the trend. In more specific terms, this study demonstrates not just a logical structure but also the development of keywords throughout time. The empirical evidence also shows that while this field initially focused on a few themes, it has since broadened to include the many aspects of urban sustainability. This analysis also identifies the most efficient and influential authors, institutions, and nations in terms of total publishing (TP), proportion of cited publications (PCP), total citation (TC), h-index, and g-index. Yang K is the most prominent author, China and the United States are the most efficient nations, and the Chinese Academy of Science is the most powerful organization. The top two nations by co-authorship are China (40 ​695 citations and 1527 publications) and the United States (41 ​119 citations and 833 publications). Additionally, it is noted that while environmental concerns continue to dominate, basic socioeconomic problems like equality, justice, and public participation are underrepresented. Sustainable development indicators, energy, ecologically friendly infrastructure, water, the use of land, and urban planning are prominent subject topics, with the first three exerting a larger influence in shaping the field's growth. This research may be utilized as a resource for people intrigued in learning more about the evaluation of urban sustainability and its advancement.